1997
DOI: 10.1111/j.1439-0434.1997.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Light and Photo‐ and Protein‐synthetic Inhibitors on the Sekiguchi Lesion Formation by Magnaporthe grisea in Rice cv. Sekiguchi‐asahi*

Abstract: The significance of light irradiation in Sekiguchi lesion (SL) formation by infection with Magnaporthe grisea on rice cv. Sekiguchi-asahi was investigated. When the leaf blades of cv. Sekiguchi-asahi inoculated with M. grisea spores were kept under different wavelengths of light. SLs were formed under visible light regardless of the compatibility between fungal race and cv. Sekiguchiasahi. On the contrary, typical blast and or nectrotic spot lesions were formed under near ultraviolet radiation from the black l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…In addition, the authors reported that phytochrome (red-light receptor) is responsible for the systemic acquired resistance. In rice plant, pathogen-induced defense responses are influenced by light conditions (Arase et al, 1997;Guo et al, 1993;Park et al, 2000). Effects of light on pathogen physiology are far less understood.…”
Section: Light-dependent Disease Suppressionmentioning
confidence: 99%
“…In addition, the authors reported that phytochrome (red-light receptor) is responsible for the systemic acquired resistance. In rice plant, pathogen-induced defense responses are influenced by light conditions (Arase et al, 1997;Guo et al, 1993;Park et al, 2000). Effects of light on pathogen physiology are far less understood.…”
Section: Light-dependent Disease Suppressionmentioning
confidence: 99%
“…Examples are the Arabidopsis lsd1 and edr1 mutants, each exhibiting resistance to both virulent bacterial and fungal pathogens (3,4). In rice, the sl mutant confers resistance to the rice blast fungus, Magnaporthe grisea (5). Similarly, the barley mlo mutant confers broad spectrum resistance to the powdery mildew fungus, Erysiphe graminis f.sp.…”
mentioning
confidence: 99%
“…Although Sekiguchi lesion formation in the light is a resistant response of sl mutants to M. grisea infection, blast lesion formation in the dark is a susceptible response (Arase et al 1997). To elucidate the mechanism underlying the light-enhanced resistance of the sl mutants to M. grisea infection, DNA fragmentation and DNase activity involved in the cell death induction were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Sekiguchi lesions were induced in leaves of the sl mutant inoculated with M. grisea spores under visible light (400-700 nm), whereas blast lesions were induced in the dark or under near-ultraviolet (UV) light (290-330 nm) (Arase et al 1997). Furthermore, infection hypha formation and sporulation of M. grisea were significantly inhibited in the Sekiguchi lesions.…”
Section: Introductionmentioning
confidence: 99%